Audio Peak Reduction Using Ultra-Short Chirps - Välimäki, Vesa; Fierro, Leonardo; Schlecht, Sebastian J.; Backman, Juha (Journal of the Audio Engineering Society, 2022)
Two filtering methods for reducing the peak value of audio signals are studied. Both methods essentially warp the signal phase while leaving its magnitude spectrum unchanged. The first technique, originally proposed by Lynch in 1988, consists of a wideband linear chirp. The listening test presented here shows that the chirp must not be longer than 4 ms, so as not to cause any audible change in timbre. The second method, called the phase rotator, put forward in 2001 by Orban and Foti is based on a cascade of second-order all-pass filters. This work proposes extensions to improve the performance of the methods, including rules to choose the parameter values. A comparison with previous methods in terms of achieved peak reduction, using a collection of short audio signals, is presented. The computational load of both methods is sufficiently low for real-time application. The extended phase rotator method is found to be superior to the linear chirp method and comparable to the other search methods. The practical peak reduction obtained with the proposed methods spans from 0 to about 3.5 dB. The signal processing methods presented in this work can increase loudness or save power in audio playback.
CRIS-Team Scopus Importer:2023-11-06